Women's organizations and democracy in South Africa : contesting authority - Hassim, Shireen (Women in Africa and the diaspora., 2006)
Examining interactions between democracy in South Africa and South African women's movement, this book explores the gendered nature of liberation and regime change. It confronts issues such as the tensions between autonomy and political dependency in feminists' engagement with the ANC and other democratic movements.